2009
DOI: 10.1111/j.1600-0447.2008.01286.x
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal gyral folding and its cognitive correlates in bipolar disorder and schizophrenia

Abstract: Patients with bipolar disorder and patients with schizophrenia have reduced prefrontal gyrification affecting both ventral and dorsal subregions. These reductions were significantly associated with cognitive impairments occurring in both disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 39 publications
5
72
0
1
Order By: Relevance
“…However, other studies reported hypogiria or preserved GI in the PFC of patients with schizophrenia (Bonnici et al, 2007;Cachia et al, 2007;Kulynych et al, 1997;Mancini-Marie et al, 2015;McIntosh et al, 2009;Nesvag et al, 2014;Palaniyappan and Liddle, 2012;Palaniyappan et al, 2011;Tepest et al, 2013;Highley et al, 2003). Possible explanations for these contrasting results could be related to the relative small sample size or to the presence of discrepancy between males and females within the patients or the control group.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…However, other studies reported hypogiria or preserved GI in the PFC of patients with schizophrenia (Bonnici et al, 2007;Cachia et al, 2007;Kulynych et al, 1997;Mancini-Marie et al, 2015;McIntosh et al, 2009;Nesvag et al, 2014;Palaniyappan and Liddle, 2012;Palaniyappan et al, 2011;Tepest et al, 2013;Highley et al, 2003). Possible explanations for these contrasting results could be related to the relative small sample size or to the presence of discrepancy between males and females within the patients or the control group.…”
Section: Discussionmentioning
confidence: 86%
“…Nevertheless, a similar general consensus on the abnormalities in gyrification asymmetry in this patients group has not been reached yet. Indeed, findings suggested either a lack or a reversed pattern of normal gyrification asimmetry in schizophrenia (Wiegand et al, 2005;Narr et al, 2004;McIntosh et al, 2009;Mancini-Marie et al, 2015;Palaniyappan et al, 2011). Therefore, given the general heterogeneity in GI literature, more research will be useful for clarifying the role of PFC gyrification asymmetry in psychosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI investigations uncovered reductions mainly in the dorsolateral prefrontal cortex in 70% of the studies reporting decreased volumes 19,20 . A further sign of early developmental deficit consists in the disturbed gyrification index as a measure of disturbed cortical folding [21][22][23][24][25] . A decreased prefrontal glucose uptake and hypofrontality has been related to negative symptoms and cognitive dysfunction 26,27 .…”
Section: Neuronal Circuits Involved In Schizophreniamentioning
confidence: 99%
“…It is possible therefore that the brain of patients with psychiatric disorders may also undergo abnormal changes during development and aging. Studies with small sample sizes have shown regional brain gyrification alterations in patients with MDD 18 , BD 19 and SCZ 20,21 . However, it is still unknown whether the lifespan trajectories of gyrification over the brain are altered in patients diagnosed with these psychiatric disorders and whether there are differential courses among them.…”
mentioning
confidence: 99%